The Prevalence and Relationship between Helicobacter pylori infection and Obesity in the Kurdish population - zjwan housein; Goran qader othman; Hawro dlawar Ismael; Beriwan Abdulqadir ali (Polytechnic Journal)
: Globally obesity is a commonly health condition. A great number of investigators have been studying the association between Helicobacter pylori (H. pylori) infection and obesity. It’s also known that H. pylori causes inflammation within the mucosa of the stomach which is known as gastritis. However, due to the arguable data in the literature, the relationship between H. Pylori and obesity remains debatable and there is no comprehensive proof for the association.